PERFORMA AYAM KUB (KAMPUNG UNGGUL BALITNAK) PERIODE STARTER PADA PEMBERIAN RANSUM DENGAN PROTEIN KASAR YANG BERBEDA - Mayora, Windara Insan; Tantalo, Syahrio; Nova, Khaira; Sutrisna, Rudy (Jurnal Riset dan Inovasi Peternakan, 2018)
This study aims to: 1) know the effect of crude protein levels of ration on performance KUB chicken starter period (age 0--4 weeks); 2) know best ration crude protein levels that affect performance KUB chicken starter period (age 0--4 weeks).  The research was conducted in May--June 2017 in the Poultry Cage Integrated Field Laboratory, Faculty of Agriculture, University of Lampung.  The method used completely randomized design (CRD) with three treatments and eight replications. Each trial unit consists of four chickens and quantity of ninety six chickens.  Treatments are: diet with high levels of coarse protein 21.50%; 18.50%; and 15.57%.  The data obtained were analyzed by using anova at 5% level and continue with BNT.  The results showed that the ration with different levels of crude protein, an effect was not significant (P> 0.05) on feed consumption, protein consumption, body weight gain, feed conversion, and Income Over Feed Cost (IOFC). Keywords: Ayam Kampung Unggul Balitnak (KUB), protein content, ration, performance.